The Implementation of KWL Chart Strategy to Improve Worldwide EFL Learners’ Reading Comprehension Skills - Wijaya, Kristian Florensio (Universitas Ma'arif Nahdlatul Ulama Kebumen, 2023)
There is a dire need for worldwide second language educators to sustainably invoke more interactive, favorable, and meaningful reading learning enterprises in which EFL learners are strongly willing to channel more effortful actions to hone their reading comprehension skills to the utmost development. KWL chart strategy can be one of the appropriate solutions to fulfill this reading learning demand by which EFL learners can activate their prior knowledge in harmony with the reading texts they are going to read, monitor their reading comprehension towards particular reading topics intensively, and profoundly evaluate their newly-acquired knowledge obtained through various passages. This present small-scale library study aimed to investigate the extent the KWL chart strategy can improve globalized EFL learners’ reading comprehension skills. 20 prior findings obtained from the KWL chart strategy in reading studies were thematically analyzed to yield more comprehensible and credible research results for the betterment of EFL reading learning enterprises nationwide. After analyzing those previous findings, two main research themes were generated namely: (1) KWL chart strategy transforms EFL learners into more spirited readers and (2) KWL chart strategy exceptionally escalates EFL learners’ reading proficiency level. In the end, it can be fairly concluded that the effective deployment of the KWL strategy not merely resulted in the significant enhancement of EFL learners’ reading comprehension skills but also their reading endeavor and knowledge. Keyword: KWL chart strategy, reading comprehension skills, EFL learners, library study, thematic analysis